SISTEM PENDIDIKAN ISLAM - Hayati , Dian; Gusmaneli, Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
Islamic religious education is education that teaches the values of goodness which then its implementation is applied in life. Islamic education itself has an important role in the history of the development of the Indonesian nation, especially in terms of the historical dimension where Islamic education has been a formal education for centuries known as pesantren. The purpose of this study is to determine the relationship, the role of Islamic education in the national education system because to make a person who is balanced from an intellectual perspective, religious education is needed, namely Islamic education in order to achieve the goals of national education. The method used in this research uses qualitative research methods with the type of library research. Based on the research results, it can be concluded that Islamic education in the national education system is Islamic education occupying a position as a formal, non-formal, informal, and religious institution. The importance of the Islamic education system that must be obtained by the Indonesian people makes Indonesia itself make regulations by organizing educational institutions based on Islamic religious education which is based on the Qur'an and Sunnah. This research uses a research method based on history, searching for books related to the material that has been given. Based on books that contain the understanding that in the Islamic education system in Indonesia. The conclusion of the discussion of the Islamic education system in Indonesia explains the definition of the Islamic education system, the components that must exist in the Islamic education system, and the discussion of the Islamic education system in Indonesia.